1999
DOI: 10.1002/(sici)1096-9896(199911)189:3<431::aid-path460>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding EGF-like growth factor is expressed by mesangial cells and is involved in mesangial proliferation in glomerulonephritis

Abstract: Heparin‐binding epidermal growth factor‐like growth factor (HB‐EGF), a new member of the EGF family, is mitogenic for several types of cells, through binding to cell surface heparan sulphate proteoglycans. This study has attempted to delineate HB‐EGF expression by mesangial cells and to identify its role in experimental and human glomerulonephritis. Rat mesangial cells, cultured in the presence of phorbol acetate, hydrogen peroxide, interleukin‐1β, and tumour necrosis factor‐α, expressed HB‐EGF mRNA. Recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Rat podocytes have been reported to show increased HB-EGF protein expression after puromycin aminonucleoside injury in the rat (37). Mesangial cells have EGF receptors and produce HB-EGF, at least in vitro (38,39). Thus, it is possible that transgene expression of hDTR might have some impact on the model even though expression of the transgene in glomeruli was at a low level and did not itself change glomerular structure or function in a measurable way.…”
Section: Discussionmentioning
confidence: 99%
“…Rat podocytes have been reported to show increased HB-EGF protein expression after puromycin aminonucleoside injury in the rat (37). Mesangial cells have EGF receptors and produce HB-EGF, at least in vitro (38,39). Thus, it is possible that transgene expression of hDTR might have some impact on the model even though expression of the transgene in glomeruli was at a low level and did not itself change glomerular structure or function in a measurable way.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1-stimulated phosphorylation of the EGF-R as well as activation of ERK1/2, and both were attenuated by the EGF-R inhibitor AG-1478. Takemura et al (61) have described the expression of HB-EGF in mesangial cells that was upregulated in experimental glomerulonephritis, a model wherein ERK1/2 is also activated. GPCR-induced transactivation of EGF-R is postulated to be in part mediated through a PKC-dependent mechanism, because the proteolytic cleavage of HB-EGF was shown to be activated by PKC (47).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a novel mechanism of EGF-R transactivation has been proposed whereby GPCR-mediated activation of Src, PYK2, and Ca 2ϩ mobilization leads to a metalloprotease proteolytic cleavage of the pro-heparinbinding (HB)-EGF precursor to yield the release of a mature ligand, which in turn activates the EGF-R (9, 32). HB-EGF-like growth factor is expressed by mesangial cells and induces cellular proliferation (61). Hence, we postulated that ET-1 signaling and downstream activation of ERK1/2 involves EGF-R transactivation.…”
mentioning
confidence: 96%
“…HB-EGF has been implicated in the pathogenesis of glomerular injury of diverse etiologies, and increased glomerular HB-EGF expression has been reported in anti-Thy-1.1 mesangial proliferative glomerulonephritis (14,16), acute puromycin aminonucleoside nephrosis (15), passive Heymann nephritis (15), anti-glomerular basement membrane glomerulonephritis (18), and experimental focal glomerular sclerosis (17). A recent study also reported increased glomerular HB-EGF expression in human biopsy material taken from patients with glomerular diseases as diverse as lupus nephritis, membranoproliferative glomerulonephritis, IgA nephropathy, and Schönlein-Henoch purpura (16). In the case of puromycin aminonucleoside nephrosis (15), increased glomerular HB-EGF expression may explain, in part, the increased glomerular HK activity reported by Dubach and Recant in this model over forty years ago (1).…”
Section: Figmentioning
confidence: 99%